Clinical and Prognostic Implications of Estimating Glomerular Filtration Rate by Three Different Creatinine-Based Equations in Older Nursing Home Residents - Paparazzo, Ersilia; Geracitano, Silvana; Lagani, Vincenzo; Soraci, Luca; Cozza, Annalisa; Cosimo, Salvatore; Morelli, Francesco; Corsonello, Andrea; Passarino, Giuseppe; Montesanto, Alberto (Frontiers in Medicine, 2022)
Background. According to the international literature, the percentage of nursing home residents with renal insufficiency is very high, ranging between 22% and 78%. Diminished kidney function represents a risk factor for drug overdosage and adverse drug reactions, end stage renal disease, disability, morbidity, and mortality. Several studies suggested that screening for CKD in high-risk and older populations may represent a cost-effective approach to reduce progression to renal failure and CKD mortality. Objective. (i) To investigate to what extent CKD may be staged interchangeably by three different creatinine-based eGFR equations in a sample of older adults living in long-term care facilities; (ii) to investigate factors explaining differences among eGFR equations; and (iii) to compare the predictivity of different creatinine-based eGFR equations with respect to all-cause mortality. Methods. A total of 522 residents aged 65 years and older participated in a retrospective cross-sectional study of 9 long-term care facilities in Calabria. eGFR was calculated by CKD-EPI, BIS and FAS equations. Disability in at least one ADL, depression, cognitive impairment, and comorbidity and malnutrition were considered in the analysis. Statistical analysis was carried out by Bland–Altman analysis and two-year mortality was investigated by Kaplan-Meier curves and Cox regression analysis. Results. Depending on the adopted equation, the prevalence of nursing home residents with impaired renal function (eGFR <60 ml/min/1.73 m2) ranged between 58.2% for the CKD-EPI and 79.1% for the BIS1 equation. The average difference between BIS and FAS was nearly negligible (0.45 mL/min/1.73 m2), while a significant bias was detected between CKD-EPI and BIS and also between CKD-EPI and FAS (6.21 mL/min/1.73 m2 and 6.65 mL/min/1.73 m2, respectively). Although the eGFR study equations had comparable prognostic accuracy in terms of mortality risk, BIS and FAS were able to reclassify NH residents pertaining a low-risk group with CKD-EPI and this reclassification improve the discriminative capacity of CKD-EPI with respect to overall mortality. Conclusion. Despite the relatively good correlation between eGFRs calculated using all adopted equations, the findings here reported clearly demonstrated that CKD-EPI and BIS/FAS equations are not interchangeable to assess eGFR among older people and particularly institutionalized and frail older subjects.